2012
DOI: 10.1175/jpo-d-11-0125.1
|View full text |Cite
|
Sign up to set email alerts
|

Horizontal Density Structure and Restratification of the Arctic Ocean Surface Layer

Abstract: Ice-tethered profiler (ITP) measurements from the Arctic Ocean's Canada Basin indicate an ocean surface layer beneath sea ice with significant horizontal density structure on scales of hundreds of kilometers to the order 1 km submesoscale. The observed horizontal gradients in density are dynamically important in that they are associated with restratification of the surface ocean when dense water flows under light water. Such restratification is prevalent in wintertime and competes with convective mixing upon b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
98
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(110 citation statements)
references
References 30 publications
9
98
3
Order By: Relevance
“…Arctic SCVs isolate and transport anomalous water properties, and have implications for transport and lateral dispersion in the Arctic. Furthermore, Timmermans et al (2012) observe restratification in the upper layers that can be attributed to lateral processes associated with sub-mesoscale features. This has consequences for maintaining the insulating stratification of the CHL.…”
Section: Sub-mesoscale Eddies Fronts and Other Processesmentioning
confidence: 90%
See 1 more Smart Citation
“…Arctic SCVs isolate and transport anomalous water properties, and have implications for transport and lateral dispersion in the Arctic. Furthermore, Timmermans et al (2012) observe restratification in the upper layers that can be attributed to lateral processes associated with sub-mesoscale features. This has consequences for maintaining the insulating stratification of the CHL.…”
Section: Sub-mesoscale Eddies Fronts and Other Processesmentioning
confidence: 90%
“…In addition, efficient lateral mixed-layer restratification also impedes mixed-layer deepening . Re-stratification as a result of sub-mesoscale (order of 1 km) instabilities within the surface layer is reported using ice-tethered profiler measurements from the Canada Basin (Timmermans et al, 2012). Previous and subsequent estimates of vertical diffusivity and heat transport therefore suggest that the warm subsurface layers in the central basins cannot contribute to significant ice melt.…”
Section: Diapycnal Mixing In the Arctic Oceanmentioning
confidence: 93%
“…This has been observed in warm regions such as the Tyrrhenian Sea in the Mediterranean [2,3] and in the western Atlantic near the Caribbean Sea [4][5][6]. Recent observations have also shown that density staircases persist over large regions of the Arctic Ocean [7][8][9][10]. It is this case that is of particular interest because the reduction in sea ice in recent years has resulted in enhanced generation of internal gravity waves (or internal waves, for short) [11,12].…”
Section: Introductionmentioning
confidence: 94%
“…Drift speeds were ~ 10 km day -1 , limiting observations to a largely temporal view of the upper ocean. Previous work by Timmermans et al (2012) show that the Canada Basin surface mixed layer can have significant horizontal density gradients during the winter season; however, the findings of Gallaher et al (2016) indicate remarkable regional consistency in salinity and temperature profiles across the upper 50 m of the ocean during the summer season (see Figure 15 of Gallaher et al, 2016). Heat budgets conducted during this study closed to within about 10%, suggesting that lateral advections were very low and that the bulk of upper ocean heat storage gains and basal ice melt were achieved by absorption of local shortwave radiative input.…”
Section: One-dimensional Analysis Of Nstmsmentioning
confidence: 99%